Raman spectroscopic characterization of stacking configuration and interlayer coupling of twisted multilayer graphene grown by chemical vapor deposition. (December 2016) - Wu, Jiang-Bin; Wang, Huan; Li, Xiao-Li; Peng, Hailin; Tan, Ping-Heng
Abstract: Multilayer graphene (MLG) grown by chemical vapor deposition (CVD) is a promising material for electronic and optoelectronic devices. Understanding the stacking configuration and interlayer coupling of MLGs is technologically relevant and of importance for the device applications. Here, we reported a kind of twisted MLGs (tMLGs), in which only one twist angle was revealed from the twist-related modes, R and R'. With increasing the total layer number of N (N > 2), the observed interlayer shear modes in the tMLG flake always follow those of AB-stacked (N-1)LG, while the observed interlayer breathing modes always follow those of AB-stacked NLG, independent of its twist angle. The tMLGs are identified as t(1+ n )LGs, which are formed by stacking one graphene monolayer on the top of AB-stacked n layer graphenes by rotating a certain angle between them. The layer breathing coupling of the t(1+ n )LGs is almost identical to that of mechanically-exfoliated tMLGs, which demonstrates the high quality of MLGs grown by CVD. This study provides an applicable approach to probe the stacking configuration and interlayer coupling of MLGs grown by CVD or related methods. This work also demonstrates the possibility to grow MLG flakes with a fixed stacking configuration, e . g ., t(1+ n )LG, by the CVD method.